THE DYNAMICS OF FACTORS ENHANCING PERFORMANCE WITH WORK CLIMATE AS AN INTERVENING VARIABLE - Sikocil, Algina Feriza; Septiano, Renil; Trismiyanti, Dessy (Komunitas Manajemen Kompetitif, 2025)
This study aims to determine and analyze the influence of leadership style on employee work climate, influence of supervision on work climate, influence of leadership style on employee performance, influence of supervision on employee performance, influence of work climate on employee performance, influence of leadership style on performance with work climate as intervening variables and the effect of supervision on performance with work climate as intervening variables. The sample in this study were lecturers at communication protocol section of Merangin District leadership. The type of data used is primary data, the data collection method uses a questionnaire with a Likert scale. Test the research instrument for validity and reliability. The data analysis technique consists of data description test, classical assumption test, path analysis and hypothesis testing. The results of the study found that leadership style has a positive and significant effect on employee work climate, supervision has a positive and significant effect on employee work climate, leadership style has a positive and significant effect on employee performance, supervision has a positive and significant effect on employee performance, work climate has a positive and significant effect. on employee performance, work climate does not play a role as an intervening variable between leadership style and employee performance and work climate does not play a role as an intervening variable between supervision and employee performance. This study suggests that to improve employee performance, a constructive leadership style, a more conducive work climate and increased supervision is needed.